Adhesive for improving poor corners of copper-clad laminate and preparation method thereof

By designing an adhesive with a specific composition and preparation method, the problem of white edges and white angles of copper clad plates is solved, and the effect of improving the heat resistance, chemical resistance and mechanical properties of the plates is achieved, reducing production costs and material waste.

CN119752380APending Publication Date: 2025-04-04KINGBOARD ELECTRONIC RAW MATERIAL (JIANG YIN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411960675.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Common white edge and white angle problems in copper clad production lead to a decline in product appearance quality, high water absorption, significant decrease in heat and chemical resistance, affecting the utilization rate of the board and increasing production costs.

Method used

An adhesive is designed to improve the poor angle of copper clad board. The raw material components include bisphenol A epoxy resin, phenolic epoxy resin, MDI modified epoxy resin, multifunctional epoxy resin monomer, curing agent, toughening agent, compound flame retardant and compound solvent. Through specific mixing ratios and preparation methods, an adhesive with good flame retardant and mechanical properties is formed.

Benefits of technology

This adhesive can effectively prevent the white edges and white angles of the copper clad plate, improve the heat and chemical resistance of the board, reduce material waste and production costs, and enhance the mechanical properties and flame retardant properties of the copper clad plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an adhesive for improving poor board corners of copper-clad laminates and a preparation method thereof, belonging to the technical field of adhesives for copper-clad laminates; the adhesive for improving poor board corners of copper-clad laminates, according to the invention, comprises raw material components, by weight, comprising 10-11 parts by weight of bisphenol A epoxy resin, 16-18 parts by weight of phenolic epoxy resin, 13-17 parts by weight of MDI modified epoxy resin, 2-3 parts by weight of multifunctional epoxy resin monomer, 0.006-0.008 parts by weight of curing agent, 18-22 parts by weight of toughening agent, 5-9 parts by weight of compound flame retardant, and 20-22 parts by weight of compound solvent; the toughening agent comprises 8-10 parts by weight of terminal hydrogen-containing silicone oil and 10-12 parts by weight of modified boron nitride; the compound flame retardant comprises 4-6 parts by weight of tetrabromobisphenol A and 1-3 parts by weight of aluminum hydroxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an adhesive for improving poor corners of copper-clad boards and a preparation method thereof. Background Art

[0002] As the PCB (printed circuit board) market becomes increasingly diversified, manufacturers are faced with the dual challenges of stabilizing product quality while reducing production costs. This trend has prompted the industry to continuously seek innovative solutions to improve product quality and efficiency. In this context, the issue of white edges and corners of copper clad laminates has become one of the key issues that need to be addressed urgently.

[0003] White edges and corners of copper clad laminates are common defects in the production of copper clad laminates and the lamination of multi-layer printed circuit boards. They are mainly manifested as white or whitish edges or corners of substrates or prepregs after lamination. Specifically, this phenomenon can be divided into two types: one is white edges, that is, the edges of the substrate appear white or whitish; the other is white corners, which refers to the corners of the substrate showing similar white or whitish characteristics. These white edges and corners not only affect the appearance quality of the product, but more importantly, they have a high water absorption rate, resulting in a significant decrease in heat resistance and chemical resistance, which cannot meet the strict requirements of PCB manufacturing. Therefore, in subsequent processing such as substrate trimming or PCB board cutting, these affected parts must be cut off, resulting in material waste, reducing the utilization rate of the board, and increasing production costs.

[0004] In order to solve the above problems, the applicant has designed an adhesive for improving the poor corners of copper clad laminates and a preparation method thereof. Summary of the invention

[0005] The purpose of the present invention is to provide an adhesive for improving the poor corners of copper clad laminates and a preparation method thereof, so as to solve the technical problems mentioned in the above background technology.

[0006] The technical solution for achieving the purpose of the present invention is: In a first aspect, the present invention provides an adhesive for improving poor corners of copper clad laminates. The raw material components include, by weight, 10 to 12 parts by weight of bisphenol A epoxy resin, 16 to 18 parts by weight of phenolic epoxy resin, 13 to 17 parts by weight of MDI modified epoxy resin, 10 to 12 parts by weight of multifunctional epoxy resin monomer, 0.006 to 0.008 parts by weight of curing agent, 18 to 22 parts by weight of toughening agent, 5 to 9 parts by weight of compound flame retardant, and 20 to 22 parts by weight of compound solvent; the compound solvent is 13 to 15 parts by weight of ethylene glycol methyl ether and 5 to 7 parts by weight of acetone.

[0007] Furthermore, the multifunctional epoxy resin monomer is obtained by polycondensing itaconic acid and glycerol and then reacting with epichlorohydrin.

[0008] Furthermore, the toughening agent includes 8-10 parts by mass of terminal hydrogen-containing silicone oil and 10-12 parts by mass of modified boron nitride.

[0009] Furthermore, the modified boron nitride is obtained by modifying boron nitride with 4-aminobenzoic acid and then chlorinating the modified boron nitride.

[0010] Furthermore, the composite flame retardant includes 4 to 6 parts by mass of tetrabromobisphenol A and 1 to 3 parts by mass of aluminum hydroxide.

[0011] In a second aspect, the present invention provides a method for preparing an adhesive for improving poor corners of copper clad laminates, comprising the following steps: (1) Under nitrogen protection, 10-12 parts by weight of a multifunctional epoxy resin monomer and a platinum catalyst are heated to 70-90° C., and then a toluene solution of a terminal hydrogenated silicone oil having a toluene content of 25-30 wt% is added dropwise, wherein the terminal hydrogenated silicone oil in the toluene solution is 8-10 parts by weight. After the addition is completed, low boiling points are removed by vacuum distillation, and then the mixture is placed in a mixture of n-hexane and tetrahydrofuran in a volume ratio of 20:1 and precipitated three times to remove the platinum catalyst, and the n-hexane and tetrahydrofuran are removed by rotary evaporation. The mixture is placed in a vacuum drying oven at 80° C. overnight to obtain a premix; (2) The premix prepared in step (1), 10 to 12 parts by weight of bisphenol A epoxy resin, 16 to 18 parts by weight of phenolic epoxy resin, 13 to 17 parts by weight of MDI modified epoxy resin, 0.006 to 0.008 parts by weight of curing agent, 10 to 12 parts by weight of modified boron nitride, 4 to 6 parts by weight of tetrabromobisphenol A, 1 to 3 parts by weight of aluminum hydroxide, 20 to 22 parts by weight of compounding solvent, and 1 to 4 parts by weight of aluminum chloride are mixed and stirred for 20 to 40 minutes to obtain an adhesive for improving poor corners of copper clad laminates.

[0012] Furthermore, the preparation steps of the multifunctional epoxy resin monomer are as follows: under nitrogen protection, 38 to 40 parts by mass of itaconic acid, 8 to 10 parts by mass of glycerol, and 80 parts by mass of toluene are mixed, the temperature is raised to 138 to 142° C., and the temperature is refluxed for 6.5 to 7.5 hours, then 91 to 94 parts by mass of epichlorohydrin are added and the temperature is raised to 108 to 112° C., and after stirring for 20 to 40 minutes, 0.08 to 0.12 parts by mass of tetrabutylammonium bromide is added, the temperature is kept for 4 to 6 hours, and then cooled to 50° C., 132 to 134 parts by mass of 30% sodium hydroxide solution is added dropwise, the temperature is kept for 1.5 to 2.5 hours, and after cooling to room temperature, it is diluted with 200 parts by mass of dichloromethane, and washed with distilled water 2 to 4 times, rotary evaporated, and vacuum concentrated to obtain a multifunctional epoxy resin monomer.

[0013] Furthermore, the preparation step of the platinum catalyst is as follows: 0.205 parts by mass of chloroplatinic acid is fully stirred and dissolved in 9.8-9.9 parts by mass of isopropanol for later use.

[0014] Furthermore, the preparation steps of the modified boron nitride are as follows: under the protection of inert gas, 8 to 12 parts by mass of boron nitride are dispersed in 200 parts by mass of an aqueous solution of 500 mg / L sodium dodecylbenzene sulfonate, and ultrasonically dispersed for 1.5 to 2.5 hours to obtain a boron nitride dispersion; 0.9 to 1 parts by mass of 4-aminobenzoic acid and 0.2 to 0.3 parts by mass of sodium hydroxide are added to 80 parts by mass of deionized water, stirred under ice bath conditions, and 0.5 to 0.55 parts by mass of sodium nitrite and 5.5 to 6.5 parts by mass of a 20wt% hydrochloric acid solution are added, stirred for 40 to 50 minutes, and then the boron nitride dispersion is added, stirred for 3.5 to 4.5 hours, followed by suction filtration, washing, and drying, and then dispersed in 100 to 200 parts by mass of anhydrous acetic acid, 3 to 4 parts by mass of phosphoryl chloride are added dropwise at 0 to 5°C, stirred for 1 to 2 hours, suction filtration, washing, and drying to obtain modified boron nitride.

[0015] Furthermore, the immersion temperature of the adhesive for improving the poor corners of the copper clad laminate is 70-80°C when used; the immersion temperature of the adhesive for improving the poor corners of the copper clad laminate is 70-80°C when used; when using the adhesive to prepare the hot pressing step of the copper clad laminate, a 3kW LED ultraviolet irradiation device is used for ultraviolet irradiation for 8-12 minutes.

[0016] By adopting the above technical solution, the present invention has the following beneficial effects: (1) The adhesive for improving the poor corners of copper clad laminates of the present invention is obtained by mixing at least the following raw material components in parts by weight: 10-12 parts by weight of bisphenol A epoxy resin, 16-18 parts by weight of phenolic epoxy resin, 13-17 parts by weight of MDI modified epoxy resin, 10-12 parts by weight of multifunctional epoxy resin monomer, 0.006-0.008 parts by weight of curing agent, 18-22 parts by weight of toughening agent, 5-9 parts by weight of compounded flame retardant, and 20-22 parts by weight of compounded solvent. The obtained adhesive for improving the poor corners of copper clad laminates has good flame retardancy and good mechanical properties, and the obtained copper clad laminates have no white edges or corners.

[0017] (2) The multifunctional epoxy resin monomer of the present invention is obtained by polycondensing itaconic acid and glycerol and then reacting with epichlorohydrin. The ester group and epoxy group introduced into the multifunctional epoxy resin monomer can form a strong interaction with the polar groups (such as hydroxyl group, carboxyl group, etc.) on the surface of the copper clad laminate substrate, thereby enhancing the bonding force between the adhesive and the substrate.

[0018] (3) The toughening agent of the present invention adopts terminal hydrogen-containing silicone oil. On the one hand, the introduction of terminal hydrogen-containing silicone oil into the epoxy resin system can form a microphase separation structure, which plays a role in stress dispersion. When subjected to external force, the terminal hydrogen-containing silicone oil can absorb and disperse energy to prevent the generation and expansion of cracks, thereby improving the impact resistance and fracture toughness of the adhesive. On the other hand, the terminal hydrogen-containing silicone oil contains active hydrogen atoms (-Si-H) at both ends, which react and cross-link with the C=C unsaturated bonds on the multifunctional epoxy resin monomer. The terminal hydrogen-containing silicone oil is grafted into the epoxy resin system, and the terminal hydrogen-containing silicone oil and the epoxy resin system are well combined, thereby increasing the impact resistance and fracture toughness of the adhesive. When the adhesive is used, bubbles appear inside the copper clad laminate. The silicone oil dispersed in the epoxy resin system can cause the bubbles to burst quickly, and the epoxy resin system quickly spreads to fill the location of the burst bubbles, thereby reducing the white edges and corners of the copper clad laminate.

[0019] (4) The toughening agent of the present invention adopts a modified boron nitride obtained by chlorinating boron nitride modified with 4-aminobenzoic acid. On the one hand, the addition of the modified boron nitride can block the flow of the adhesive, thereby reducing the white edges and corners of the copper clad laminate. On the other hand, the modified boron nitride has good dispersibility in the epoxy resin system, thereby avoiding the influence of boron nitride agglomeration on the mechanical properties of the copper clad laminate and improving the adhesive with poor corners of the copper clad laminate. In the process of preparing the copper clad laminate, an immersion temperature of 70 to 80° C. is used. Under the action of the catalyst aluminum chloride, the benzoyl chloride on the chlorinated 4-aminobenzoic acid reacts with the The benzene ring in the epoxy resin system is reacted and grafted to form a benzophenone derivative. In the process of preparing the copper clad laminate, it is first subjected to light treatment before hot pressing. The benzophenone derivative triggers the polymerization of the remaining unsaturated bonds in the epoxy system under light, increases the cross-linking density of the adhesive that improves the poor corners of the copper clad laminate, and further has a blocking effect on the flow of the adhesive, thereby enhancing the mechanical properties of the copper clad laminate and further reducing the white edges and corners of the copper clad laminate. On the other hand, when burning, it synergizes with the compound flame retardant to form an effective insulation layer on the surface of the burning material during combustion, thereby enhancing the flame retardancy of the adhesive. DETAILED DESCRIPTION

[0020] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.

[0021] The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the protection scope of the present invention.

[0022] The raw materials of the embodiments of the present invention and the comparative examples are as follows: Bisphenol A resin, phenolic epoxy resin, and MDI modified epoxy resin were KBJS-505BX80 with a solid content of 80%, SQAN-203EK70 with a solid content of 70%, and KBJS-2350BN70 with a solid content of 70%, respectively, produced by Jiantao (Jiangsu) Chemical Co., Ltd.; The curing agent uses 2MZ-A imidazole epoxy curing agent; End-hydrogenated silicone oil, hydrogen content is 0.24 mol·(100 g) -1 , Mn=300~500; The preparation steps of the platinum catalyst are as follows: 0.205 parts by mass of chloroplatinic acid is fully stirred and dissolved in 9.88 parts by mass of isopropanol, and the mixture is set aside.

[0023] (Example 1) A method for preparing an adhesive for improving poor corners of copper-clad laminates comprises the following steps: (1) Under nitrogen protection, 10 parts by weight of a multifunctional epoxy resin monomer and a platinum catalyst are heated to 70°C, and then a toluene solution of a terminal hydrogenated silicone oil having a toluene content of 25 wt% is added dropwise, wherein the terminal hydrogenated silicone oil in the toluene solution is 8 parts by weight. After the addition is completed, low boiling points are removed by vacuum distillation, and then the mixture is placed in a mixture of n-hexane and tetrahydrofuran in a volume ratio of 20:1 and precipitated three times to remove the platinum catalyst. The n-hexane and tetrahydrofuran are removed by rotary evaporation, and the mixture is placed in a vacuum drying oven at 80°C overnight to obtain a premix; the amount of the platinum catalyst used is 30 ppm; (2) The premix prepared in step (1), 10 parts by mass of bisphenol A epoxy resin, 16 parts by mass of phenolic epoxy resin, 13 parts by mass of MDI modified epoxy resin, 0.006 parts by mass of curing agent, 10 parts by mass of modified boron nitride, 4 parts by mass of tetrabromobisphenol A, 1 part by mass of aluminum hydroxide, 20 parts by mass of compounding solvent, and 1 part by mass of aluminum chloride are mixed and stirred for 20 minutes to obtain an adhesive for improving the poor corners of copper clad laminates.

[0024] The preparation steps of the multifunctional epoxy resin monomer are as follows: under nitrogen protection, 38 parts by mass of itaconic acid, 8 parts by mass of glycerol and 80 parts by mass of toluene are mixed, the temperature is raised to 138° C. and refluxed for reaction for 6.5 hours, then 91 parts by mass of epichlorohydrin are added and the temperature is raised to 108° C., after stirring for 20 minutes, 0.08 parts by mass of tetrabutylammonium bromide is added, the temperature is kept for reaction for 4 hours, and then the temperature is cooled to 50° C., 132 parts by mass of 30% sodium hydroxide solution is added dropwise, the temperature is kept for reaction for 1.5 hours, and after cooling to room temperature, it is diluted with 200 parts by mass of dichloromethane, washed with distilled water twice, rotary evaporated and vacuum concentrated to obtain a multifunctional epoxy resin monomer.

[0025] The preparation steps of modified boron nitride are as follows: under the protection of inert gas, 8 parts by mass of boron nitride are dispersed in 200 parts by mass of an aqueous solution of 500 mg / L sodium dodecylbenzene sulfonate, and ultrasonically dispersed for 1.5 hours to obtain a boron nitride dispersion; 0.9 parts by mass of 4-aminobenzoic acid and 0.2 parts by mass of sodium hydroxide are added to 80 parts by mass of deionized water, stirred under ice bath conditions, and 0.5 parts by mass of sodium nitrite and 5.5 parts by mass of a 20wt% hydrochloric acid solution are added, stirred for 40 minutes, and then the boron nitride dispersion is added, stirred for 3.5 hours, followed by suction filtration, washing, and drying, and then dispersed in 100 parts by mass of anhydrous acetic acid, 3 parts by mass of phosphoryl chloride are added dropwise at 0°C, stirred for 1 hour, suction filtration, washing, and drying are performed to obtain modified boron nitride.

[0026] (Example 2) A method for preparing an adhesive for improving poor corners of copper-clad laminates comprises the following steps: (1) Under nitrogen protection, 11 parts by weight of a multifunctional epoxy resin monomer and a platinum catalyst are heated to 80°C, and then a toluene solution of a terminal hydrogenated silicone oil having a toluene content of 28 wt% is added dropwise, wherein the terminal hydrogenated silicone oil in the toluene solution is 9 parts by weight. After the addition is completed, low boiling points are removed by vacuum distillation, and then the mixture is placed in a mixture of n-hexane and tetrahydrofuran in a volume ratio of 20:1 and precipitated three times to remove the platinum catalyst. The n-hexane and tetrahydrofuran are removed by rotary evaporation, and the mixture is placed in a vacuum drying oven at 80°C overnight to obtain a premix; the amount of the platinum catalyst used is 30 ppm; (2) The premix prepared in step (1), 11 parts by mass of bisphenol A epoxy resin, 17 parts by mass of phenolic epoxy resin, 15 parts by mass of MDI modified epoxy resin, 0.007 parts by mass of curing agent, 11 parts by mass of modified boron nitride, 5 parts by mass of tetrabromobisphenol A, 2 parts by mass of aluminum hydroxide, 21 parts by mass of compounding solvent, and 3 parts by mass of aluminum chloride are mixed and stirred for 30 minutes to obtain an adhesive for improving the poor corners of copper clad laminates.

[0027] The preparation steps of the multifunctional epoxy resin monomer are as follows: under nitrogen protection, 39 parts by mass of itaconic acid, 9 parts by mass of glycerol and 80 parts by mass of toluene are mixed, the temperature is raised to 140° C. and refluxed for reaction for 7 hours, then 93 parts by mass of epichlorohydrin are added and the temperature is raised to 110° C., after stirring for 30 minutes, 0.1 parts by mass of tetrabutylammonium bromide is added, the temperature is kept for reaction for 5 hours, and then the temperature is cooled to 50° C., 133 parts by mass of 30% sodium hydroxide solution is added dropwise, the temperature is kept for reaction for 2 hours, and after cooling to room temperature, it is diluted with 200 parts by mass of dichloromethane, washed with distilled water for 3 times, rotary evaporated and vacuum concentrated to obtain a multifunctional epoxy resin monomer.

[0028] The preparation steps of modified boron nitride are as follows: under the protection of inert gas, 10 parts by mass of boron nitride are dispersed in 200 parts by mass of an aqueous solution of 500 mg / L sodium dodecylbenzene sulfonate, and ultrasonically dispersed for 2 hours to obtain a boron nitride dispersion; 0.96 parts by mass of 4-aminobenzoic acid and 0.25 parts by mass of sodium hydroxide are added to 80 parts by mass of deionized water, stirred under ice bath conditions, and 0.53 parts by mass of sodium nitrite and 6 parts by mass of a 20wt% hydrochloric acid solution are added, stirred for 45 minutes, and then the boron nitride dispersion is added, stirred for 4 hours, followed by suction filtration, washing, and drying, and then dispersed in 150 parts by mass of anhydrous acetic acid, 3.5 parts by mass of phosphoryl chloride are added dropwise at 3°C, stirred for 1.5 hours, suction filtration, washing, and drying are performed to obtain modified boron nitride.

[0029] (Example 3) A method for preparing an adhesive for improving poor corners of copper-clad laminates comprises the following steps: (1) Under nitrogen protection, 12 parts by weight of a multifunctional epoxy resin monomer and a platinum catalyst are heated to 90° C., and then a toluene solution of a terminal hydrogenated silicone oil having a toluene content of 30 wt% is added dropwise, wherein the terminal hydrogenated silicone oil in the toluene solution is 10 parts by weight. After the addition is completed, low-boiling substances are removed by vacuum distillation, and then the mixture is placed in a mixture of n-hexane and tetrahydrofuran having a volume ratio of 20:1 and precipitated three times to remove the platinum catalyst. The n-hexane and tetrahydrofuran are removed by rotary evaporation, and the mixture is placed in a vacuum drying oven at 80° C. overnight to obtain a premix; the amount of the platinum catalyst used is 30 ppm; (2) The premix prepared in step (1), 12 parts by mass of bisphenol A epoxy resin, 18 parts by mass of phenolic epoxy resin, 17 parts by mass of MDI modified epoxy resin, 0.008 parts by mass of curing agent, 12 parts by mass of modified boron nitride, 6 parts by mass of tetrabromobisphenol A, 3 parts by mass of aluminum hydroxide, 22 parts by mass of compounding solvent, and 4 parts by mass of aluminum trichloride were mixed and stirred for 40 minutes to obtain an adhesive for improving the poor corners of copper clad laminates.

[0030] The preparation steps of the multifunctional epoxy resin monomer are as follows: under nitrogen protection, 40 parts by mass of itaconic acid, 10 parts by mass of glycerol and 80 parts by mass of toluene are mixed, the temperature is raised to 142° C. and refluxed for reaction for 7.5 hours, then 94 parts by mass of epichlorohydrin are added and the temperature is raised to 112° C., after stirring for 40 minutes, 0.12 parts by mass of tetrabutylammonium bromide is added, the temperature is kept for reaction for 6 hours, and then the temperature is cooled to 50° C., 134 parts by mass of 30% sodium hydroxide solution is added dropwise, the temperature is kept for reaction for 2.5 hours, and after cooling to room temperature, it is diluted with 200 parts by mass of dichloromethane, washed with distilled water for 4 times, rotary evaporated and vacuum concentrated to obtain a multifunctional epoxy resin monomer.

[0031] The preparation steps of modified boron nitride are as follows: under the protection of inert gas, 12 parts by mass of boron nitride are dispersed in 200 parts by mass of an aqueous solution of 500 mg / L sodium dodecylbenzene sulfonate, and ultrasonically dispersed for 2.5 hours to obtain a boron nitride dispersion; 1 part by mass of 4-aminobenzoic acid and 0.3 parts by mass of sodium hydroxide are added to 80 parts by mass of deionized water, stirred under ice bath conditions, and 0.55 parts by mass of sodium nitrite and 6.5 parts by mass of a 20wt% hydrochloric acid solution are added, stirred for reaction for 50 minutes, and then the boron nitride dispersion is added, stirred for reaction for 4.5 hours, followed by suction filtration, washing, and drying, and then dispersed in 200 parts by mass of anhydrous acetic acid, 4 parts by mass of phosphoryl chloride are added dropwise at 5°C, stirred for reaction for 2 hours, suction filtration, washing, and drying to obtain modified boron nitride.

[0032] (Comparative Example 1) A method for preparing an adhesive for improving poor corners of copper-clad laminates comprises the following steps: (1) Under nitrogen protection, 11 parts by weight of a multifunctional epoxy resin monomer and a platinum catalyst are heated to 80°C, and then a toluene solution of a terminal hydrogenated silicone oil having a toluene content of 28 wt% is added dropwise, wherein the terminal hydrogenated silicone oil in the toluene solution is 9 parts by weight. After the addition is completed, low boiling points are removed by vacuum distillation, and then the mixture is placed in a mixture of n-hexane and tetrahydrofuran in a volume ratio of 20:1 and precipitated three times to remove the platinum catalyst. The n-hexane and tetrahydrofuran are removed by rotary evaporation, and the mixture is placed in a vacuum drying oven at 80°C overnight to obtain a premix; the amount of the platinum catalyst used is 30 ppm; (2) The premix prepared in step (1), 11 parts by mass of bisphenol A epoxy resin, 17 parts by mass of phenolic epoxy resin, 15 parts by mass of MDI modified epoxy resin, 0.007 parts by mass of curing agent, 11 parts by mass of boron nitride, 5 parts by mass of tetrabromobisphenol A, 2 parts by mass of aluminum hydroxide, 21 parts by mass of compounding solvent, and 3 parts by mass of aluminum chloride are mixed and stirred for 30 minutes to obtain an adhesive for improving the poor corners of copper clad laminates.

[0033] The preparation steps of the multifunctional epoxy resin monomer are as follows: under nitrogen protection, 39 parts by mass of itaconic acid, 9 parts by mass of glycerol and 80 parts by mass of toluene are mixed, the temperature is raised to 140° C. and refluxed for reaction for 7 hours, then 93 parts by mass of epichlorohydrin are added and the temperature is raised to 110° C., after stirring for 30 minutes, 0.1 parts by mass of tetrabutylammonium bromide is added, the temperature is kept for reaction for 5 hours, and then the temperature is cooled to 50° C., 133 parts by mass of 30% sodium hydroxide solution is added dropwise, the temperature is kept for reaction for 2 hours, and after cooling to room temperature, it is diluted with 200 parts by mass of dichloromethane, washed with distilled water for 3 times, rotary evaporated and vacuum concentrated to obtain a multifunctional epoxy resin monomer.

[0034] (Comparative Example 2) A method for preparing an adhesive for improving poor corners of copper-clad laminates comprises the following steps: (1) Under nitrogen protection, 11 parts by weight of a multifunctional epoxy resin monomer and a platinum catalyst are heated to 80°C, and then a toluene solution of a terminal hydrogenated silicone oil having a toluene content of 28 wt% is added dropwise, wherein the terminal hydrogenated silicone oil in the toluene solution is 9 parts by weight. After the addition is completed, low boiling points are removed by vacuum distillation, and then the mixture is placed in a mixture of n-hexane and tetrahydrofuran in a volume ratio of 20:1 and precipitated three times to remove the platinum catalyst. The n-hexane and tetrahydrofuran are removed by rotary evaporation, and the mixture is placed in a vacuum drying oven at 80°C overnight to obtain a premix; the amount of the platinum catalyst used is 30 ppm; (2) The premix prepared in step (1), 11 parts by weight of bisphenol A epoxy resin, 17 parts by weight of phenolic epoxy resin, 15 parts by weight of MDI modified epoxy resin, 0.007 parts by weight of curing agent, 5 parts by weight of tetrabromobisphenol A, 2 parts by weight of aluminum hydroxide, 21 parts by weight of compounding solvent, and 3 parts by weight of aluminum chloride were mixed and stirred for 30 minutes to obtain an adhesive for improving the poor corners of copper clad laminates.

[0035] The preparation steps of the multifunctional epoxy resin monomer are as follows: under nitrogen protection, 39 parts by mass of itaconic acid, 9 parts by mass of glycerol and 80 parts by mass of toluene are mixed, the temperature is raised to 140° C. and refluxed for reaction for 7 hours, then 93 parts by mass of epichlorohydrin are added and the temperature is raised to 110° C., after stirring for 30 minutes, 0.1 parts by mass of tetrabutylammonium bromide is added, the temperature is kept for reaction for 5 hours, and then the temperature is cooled to 50° C., 133 parts by mass of 30% sodium hydroxide solution is added dropwise, the temperature is kept for reaction for 2 hours, and after cooling to room temperature, it is diluted with 200 parts by mass of dichloromethane, washed with distilled water for 3 times, rotary evaporated and vacuum concentrated to obtain a multifunctional epoxy resin monomer.

[0036] (Comparative Example 3) A method for preparing an adhesive for improving poor corners of copper-clad laminates comprises the following steps: (1) 11 parts by mass of multifunctional epoxy resin monomer, 11 parts by mass of bisphenol A epoxy resin, 17 parts by mass of phenolic epoxy resin, 15 parts by mass of MDI modified epoxy resin, 0.007 parts by mass of curing agent, 11 parts by mass of modified boron nitride, 5 parts by mass of tetrabromobisphenol A, 2 parts by mass of aluminum hydroxide, 21 parts by mass of compound solvent and 3 parts by mass of aluminum trichloride were mixed and stirred for 30 minutes to obtain an adhesive for improving the poor corners of copper clad laminates.

[0037] The preparation steps of the multifunctional epoxy resin monomer are as follows: under nitrogen protection, 39 parts by mass of itaconic acid, 9 parts by mass of glycerol and 80 parts by mass of toluene are mixed, the temperature is raised to 140° C. and refluxed for reaction for 7 hours, then 93 parts by mass of epichlorohydrin are added and the temperature is raised to 110° C., after stirring for 30 minutes, 0.1 parts by mass of tetrabutylammonium bromide is added, the temperature is kept for reaction for 5 hours, and then the temperature is cooled to 50° C., 133 parts by mass of 30% sodium hydroxide solution is added dropwise, the temperature is kept for reaction for 2 hours, and after cooling to room temperature, it is diluted with 200 parts by mass of dichloromethane, washed with distilled water for 3 times, rotary evaporated and vacuum concentrated to obtain a multifunctional epoxy resin monomer.

[0038] The preparation steps of modified boron nitride are as follows: under the protection of inert gas, 10 parts by mass of boron nitride are dispersed in 200 parts by mass of an aqueous solution of 500 mg / L sodium dodecylbenzene sulfonate, and ultrasonically dispersed for 2 hours to obtain a boron nitride dispersion; 0.96 parts by mass of 4-aminobenzoic acid and 0.25 parts by mass of sodium hydroxide are added to 80 parts by mass of deionized water, stirred under ice bath conditions, and 0.53 parts by mass of sodium nitrite and 6 parts by mass of a 20wt% hydrochloric acid solution are added, stirred for 45 minutes, and then the boron nitride dispersion is added, stirred for 4 hours, followed by suction filtration, washing, and drying, and then dispersed in 150 parts by mass of anhydrous acetic acid, 3.5 parts by mass of phosphoryl chloride are added dropwise at 3°C, stirred for 1.5 hours, suction filtration, washing, and drying are performed to obtain modified boron nitride.

[0039] (Comparative Example 4) A method for preparing an adhesive for improving poor corners of copper-clad laminates comprises the following steps: (1) 11 parts by weight of multifunctional epoxy resin monomer, 9 parts by weight of end-hydrogenated silicone oil, 11 parts by weight of bisphenol A epoxy resin, 17 parts by weight of novolac epoxy resin, 15 parts by weight of MDI modified epoxy resin, 0.007 parts by weight of curing agent, 11 parts by weight of modified boron nitride, 5 parts by weight of tetrabromobisphenol A, 2 parts by weight of aluminum hydroxide, 21 parts by weight of compound solvent and 3 parts by weight of aluminum chloride were mixed and stirred for 30 minutes to obtain an adhesive for improving the poor corners of copper clad laminates.

[0040] The preparation steps of the multifunctional epoxy resin monomer are as follows: under nitrogen protection, 39 parts by mass of itaconic acid, 9 parts by mass of glycerol and 80 parts by mass of toluene are mixed, the temperature is raised to 140° C. and refluxed for reaction for 7 hours, then 93 parts by mass of epichlorohydrin are added and the temperature is raised to 110° C., after stirring for 30 minutes, 0.1 parts by mass of tetrabutylammonium bromide is added, the temperature is kept for reaction for 5 hours, and then the temperature is cooled to 50° C., 133 parts by mass of 30% sodium hydroxide solution is added dropwise, the temperature is kept for reaction for 2 hours, and after cooling to room temperature, it is diluted with 200 parts by mass of dichloromethane, washed with distilled water for 3 times, rotary evaporated and vacuum concentrated to obtain a multifunctional epoxy resin monomer.

[0041] The preparation steps of modified boron nitride are as follows: under the protection of inert gas, 10 parts by mass of boron nitride are dispersed in 200 parts by mass of an aqueous solution of 500 mg / L sodium dodecylbenzene sulfonate, and ultrasonically dispersed for 2 hours to obtain a boron nitride dispersion; 0.96 parts by mass of 4-aminobenzoic acid and 0.25 parts by mass of sodium hydroxide are added to 80 parts by mass of deionized water, stirred under ice bath conditions, and 0.53 parts by mass of sodium nitrite and 6 parts by mass of a 20wt% hydrochloric acid solution are added, stirred for 45 minutes, and then the boron nitride dispersion is added, stirred for 4 hours, followed by suction filtration, washing, and drying, and then dispersed in 150 parts by mass of anhydrous acetic acid, 3.5 parts by mass of phosphoryl chloride are added dropwise at 3°C, stirred for 1.5 hours, suction filtration, washing, and drying are performed to obtain modified boron nitride.

[0042] (Comparative Example 5) A method for preparing an adhesive for improving poor corners of copper-clad laminates comprises the following steps: (1) Under nitrogen protection, 11 parts by weight of multifunctional epoxy resin monomer glycidyl ether and platinum catalyst are heated to 80°C, and then a toluene solution of terminal hydrogenated silicone oil with a toluene content of 28 wt% is added dropwise, wherein the terminal hydrogenated silicone oil in the toluene solution is 9 parts by weight. After the addition is completed, low boiling points are removed by vacuum distillation, and then the mixture is placed in a mixture of n-hexane and tetrahydrofuran with a volume ratio of 20:1 and precipitated three times to remove the platinum catalyst. The n-hexane and tetrahydrofuran are removed by rotary evaporation, and the mixture is placed in a vacuum drying oven at 80°C overnight to obtain a premix; the amount of platinum catalyst used is 30 ppm; (2) The premix prepared in step (1), 11 parts by mass of bisphenol A epoxy resin, 17 parts by mass of phenolic epoxy resin, 15 parts by mass of MDI modified epoxy resin, 0.007 parts by mass of curing agent, 11 parts by mass of modified boron nitride, 5 parts by mass of tetrabromobisphenol A, 2 parts by mass of aluminum hydroxide, 21 parts by mass of compounding solvent, and 3 parts by mass of aluminum chloride are mixed and stirred for 30 minutes to obtain an adhesive for improving the poor corners of copper clad laminates.

[0043] The preparation steps of modified boron nitride are as follows: under the protection of inert gas, 10 parts by mass of boron nitride are dispersed in 200 parts by mass of an aqueous solution of 500 mg / L sodium dodecylbenzene sulfonate, and ultrasonically dispersed for 2 hours to obtain a boron nitride dispersion; 0.96 parts by mass of 4-aminobenzoic acid and 0.25 parts by mass of sodium hydroxide are added to 80 parts by mass of deionized water, stirred under ice bath conditions, and 0.53 parts by mass of sodium nitrite and 6 parts by mass of a 20wt% hydrochloric acid solution are added, stirred for 45 minutes, and then the boron nitride dispersion is added, stirred for 4 hours, followed by suction filtration, washing, and drying, and then dispersed in 150 parts by mass of anhydrous acetic acid, 3.5 parts by mass of phosphoryl chloride are added dropwise at 3°C, stirred for 1.5 hours, suction filtration, washing, and drying are performed to obtain modified boron nitride.

[0044] Effect example The adhesive for improving the poor corner of the copper clad laminate prepared in the embodiment and the comparative example is uniformly rolled on the glass fiber cloth to obtain a prepreg cloth; the roll coating amount of the adhesive solution is: 210g of adhesive solution is rolled on each square meter of the glass fiber cloth; in this embodiment, the glass fiber cloth and the adhesive solution are preheated before rolling, so that the preheated glass fiber cloth and the adhesive solution have a temperature of 80°C; an LED with a power of 3kW is used The prepreg is irradiated with ultraviolet light by an ultraviolet irradiation device for 10 minutes to obtain a semi-cured sheet; copper foil is laid on the semi-cured sheet, and then put into a hot press for hot pressing curing treatment, wherein the hot pressing curing treatment adopts a three-stage hot pressing curing treatment, specifically: heating from a room temperature of 25°C, and applying pressure while heating, so that the semi-cured sheet with copper foil is kept at a constant temperature and pressure of 80°C and a pressure of 0.49MPa for 10 minutes for the first stage of hot pressing curing treatment, and then heating at 1.2°C / min, and applying pressure while heating, so that the semi-cured sheet with copper foil is kept at a constant temperature and pressure of 140°C and a pressure of 0.98MPa for 30 minutes for the second stage of hot pressing curing treatment, and then continuing to heat and pressurize while heating, so that the semi-cured sheet with copper foil is kept at a constant temperature and pressure of 160°C and a pressure of 1.47MPa for 65 minutes, and finally releasing the pressure and cooling to obtain a copper clad laminate.

[0045] The test items include peel strength (IPC-TM-650 2.4.8); flammability (UL94); bending strength (IPC-TM-650 2.4.4); appearance performance: observe whether there are white edges, white corners or white spots on the copper clad laminate.

[0046] Toughness: Use an impact tester with a drop height of 45cm and a drop weight of 1kg. Good or bad toughness evaluation: A clear cross indicates better toughness of the product, indicated by character ①; a blurred cross indicates poor toughness and high brittleness of the product, indicated by character ②; a cross with a clarity between clear and blurred indicates average toughness of the product, indicated by character ③.

[0047] Table 1 below shows the performance test results of adhesives for improving the corner defects of copper clad laminates prepared in the embodiments of the present invention and the comparative examples: Table 1

[0048] It can be seen from Table 1 that the copper clad laminate prepared with the adhesive for improving the poor corners of the copper clad laminate prepared in the embodiment has good peel strength, impact resistance, flame retardancy and mechanical properties, and there are no white edges, white corners or white spots in the copper clad laminate.

[0049] The only difference between Comparative Example 1 and Example 2 is that the boron nitride in Comparative Example 1 is not modified, and the impact resistance, flame retardancy, and mechanical properties of the resulting copper clad laminate are poor, and a large number of white spots exist, because the dispersibility of boron nitride is poor.

[0050] The only difference between Comparative Example 2 and Example 2 is that no modified boron nitride is added in Comparative Example 2, and the impact resistance, flame retardancy and mechanical properties of the obtained copper clad laminate are poor, and there are white edges.

[0051] The only difference between Comparative Example 3 and Example 2 is that no end-hydrogenated silicone oil is added in Comparative Example 3, and the resulting copper clad laminate has poor impact resistance and mechanical properties, and has white edges, white corners and white spots.

[0052] The only difference between Comparative Example 4 and Example 2 is that in Comparative Example 4, the multifunctional epoxy resin monomer and the terminal hydrogen-containing silicone oil are not pre-mixed, and the mechanical properties of the obtained copper clad laminate are poor.

[0053] The only difference between Comparative Example 5 and Example 2 is that the multifunctional epoxy resin monomer in Comparative Example 5 adopts glycerol ether, and the peel strength and mechanical properties of the obtained copper clad laminate are poor.

[0054] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An adhesive for improving the poor corners of copper clad laminates, characterized in that: In terms of weight, the raw material components include 10 to 12 parts by weight of bisphenol A epoxy resin, 16 to 18 parts by weight of phenolic epoxy resin, 13 to 17 parts by weight of MDI modified epoxy resin, 10 to 12 parts by weight of multifunctional epoxy resin monomer, 0.006 to 0.008 parts by weight of curing agent, 18 to 22 parts by weight of toughening agent, 5 to 9 parts by weight of compound flame retardant, and 20 to 22 parts by weight of compound solvent.

2. The adhesive for improving the poor corners of copper clad laminates according to claim 1, characterized in that: The multifunctional epoxy resin monomer is obtained by polycondensing itaconic acid and glycerol and then reacting with epichlorohydrin.

3. The adhesive for improving the poor corners of copper clad laminates according to claim 1, characterized in that: The toughening agent includes 8-10 parts by weight of terminal hydrogen-containing silicone oil and 10-12 parts by weight of modified boron nitride.

4. The adhesive for improving the poor corners of copper clad laminates according to claim 1, characterized in that: The modified boron nitride is obtained by modifying boron nitride with 4-aminobenzoic acid and then chlorinating the modified boron nitride.

5. The adhesive for improving the poor corners of copper clad laminates according to claim 1, characterized in that: The composite flame retardant comprises 4-6 parts by mass of tetrabromobisphenol A and 1-3 parts by mass of aluminum hydroxide.

6. A method for preparing an adhesive for improving poor corners of copper-clad laminates, characterized in that: The following steps are involved: (1) Under nitrogen protection, 10-12 parts by weight of a multifunctional epoxy resin monomer and a platinum catalyst are heated to 70-90° C., and then a toluene solution of a terminal hydrogenated silicone oil having a toluene content of 25-30 wt% is added dropwise, wherein the terminal hydrogenated silicone oil in the toluene solution is 8-10 parts by weight. After the addition is completed, low boiling points are removed by vacuum distillation, and then the mixture is placed in a mixture of n-hexane and tetrahydrofuran in a volume ratio of 20:1 and precipitated three times to remove the platinum catalyst, and the n-hexane and tetrahydrofuran are removed by rotary evaporation. The mixture is placed in a vacuum drying oven at 80° C. overnight to obtain a premix; (2) The premix prepared in step (1), 10 to 12 parts by weight of bisphenol A epoxy resin, 16 to 18 parts by weight of phenolic epoxy resin, 13 to 17 parts by weight of MDI modified epoxy resin, 0.006 to 0.008 parts by weight of curing agent, 10 to 12 parts by weight of modified boron nitride, 4 to 6 parts by weight of tetrabromobisphenol A, 1 to 3 parts by weight of aluminum hydroxide, and 20 to 22 parts by weight of compound solvent are mixed and stirred and dispersed for 20 to 40 minutes to obtain an adhesive for improving poor corners of copper clad laminates.

7. The method for preparing an adhesive for improving poor corners of copper clad laminates according to claim 6, characterized in that: The preparation steps of the multifunctional epoxy resin monomer are as follows: under nitrogen protection, 38-40 parts by weight of itaconic acid, 8-10 parts by weight of glycerol and 80 parts by weight of toluene are mixed, the temperature is raised to 138-142° C., and the mixture is refluxed for reaction for 6.5-7.5 hours, then 91-94 parts by weight of epichlorohydrin is added, the temperature is raised to 108-112° C., and after stirring for 20-40 minutes, 0.08-0.12 parts by weight of tetrabutylammonium bromide is added, the mixture is kept warm for reaction for 4-6 hours, and then cooled to 50° C., 132-134 parts by weight of a 30% sodium hydroxide solution is added dropwise, the mixture is kept warm for reaction for 1.5-2.5 hours, and after cooling to room temperature, the mixture is diluted with 200 parts by weight of dichloromethane, and the mixture is washed with distilled water for 2-4 times, and the mixture is rotary evaporated and vacuum concentrated to obtain a multifunctional epoxy resin monomer.

8. The method for preparing an adhesive for improving poor corners of copper clad laminates according to claim 6, characterized in that: The preparation steps of the platinum catalyst are as follows: 0.205 parts by mass of chloroplatinic acid is fully stirred and dissolved in 9.8-9.9 parts by mass of isopropanol for later use.

9. The method for preparing an adhesive for improving poor corners of copper clad laminates according to claim 6, characterized in that: The preparation steps of the modified boron nitride are as follows: under the protection of inert gas, 8-12 parts by mass of boron nitride are dispersed in 200 parts by mass of an aqueous solution of 500 mg / L sodium dodecylbenzene sulfonate, and ultrasonically dispersed for 1.5-2.5 hours to obtain a boron nitride dispersion; 0.9-1 parts by mass of 4-aminobenzoic acid and 0.2-0.3 parts by mass of sodium hydroxide are added to 80 parts by mass of deionized water, stirred under ice bath conditions, and 0.5-0.55 parts by mass of sodium nitrite and 5.5-6.5 parts by mass of a 20wt% hydrochloric acid solution are added, stirred for 40-50 minutes, and then the boron nitride dispersion is added, stirred for 3.5-4.5 hours, followed by suction filtration, washing, and drying, and then dispersed in 100-200 parts by mass of anhydrous acetic acid, 3-4 parts by mass of phosphoryl chloride are added dropwise at 0-5°C, stirred for 1-2 hours, suction filtration, washing, and drying are performed to obtain modified boron nitride.

10. The method for preparing an adhesive for improving poor corners of copper clad laminates according to claim 6, characterized in that: The immersion temperature of the adhesive for improving the poor corners of copper-clad laminates is 70-80° C. during use; and a 3kW LED ultraviolet irradiation device is used for ultraviolet irradiation for 8-12 minutes during the hot pressing step of preparing copper-clad laminates using the adhesive.